Pemilihan Alternatif Simplisia Nabati Untuk Indikasi Gangguan Kesehatan Menggunakan Metode Analytical Network Process (ANP) dan Simple Additive Weighting (SAW) - Gessia Faradiksi Putri; Lailil Muflikhah; Sigit Adinugroho (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Medicinal plants are one of natural resources that is rarely known by Indonesian. Medicinal plants, known as simplicia, have various health benefits. What people know about simplicia is still very low, so they tend to choose modern medicines which costs much more than simplicia. In fact, simplicia is also safe and can save cost. But, because there are so many alternatives, eventually people become confused to choose which one is the most suitable for them. The parameters used to choose simplicia alternatives are the price, taste, availability of materials and nutritious substances. These parameters are used as references for choosing simplicia alternatives. This research uses Analytical Network Process (ANP) and Simple Additive Weighting (SAW) methods which are used for weighting and ranking. The ranking result obtained by ANP and SAW methods has accuracy on fever 40%, diarrhea 50% and cough 40%. The low tendency accuracy is caused by different usage of criteria weighting between target data and outcomes as well as the influence of innerdepence between criteria.